Representing Trauma. Post-memory and ethics of representation in Art Spiegelman's Maus (Anclajes, 2022)
Due to the originality of its aesthetic approach in representing a traumatic testimony, Art Spiegelman's graphic novel Maus is one of the most famous works about the Holocaust produced by the post-memory generation. Within the currents of thought on the Holocaust, it is possible to conceive its style of representation as a pertinent and ethically valid solution to the dilemma of images v. testimony. Likewise, it is worth noting how its essentially fragmented, narrative approach reflects conditions in which the work was created: the scarcity of sources and the traumatic and familiar component of the memory represented.
Keywords: 20th century; Poland; Spiegelman; Graphic novel; Post-memory